Motivasi Penglibatan Rekreasi Luar Dalam Kalangan Masyarakat Luar Bandar Dan Bandar Di Ipoh, Perak - Dulhamid, Hasnizam Ab (2023)
Outdoor recreational activities are considered as a significant part of human daily life because of the beneficial outcomes it brings for a healthy lifestyle among communities. The popularity of recreational activities must be maintained as it is seen as an important factor that can influence the future of professional industrial sectors and economic development. Although ample studies have shown the profound benefits of recreational activities, the Malaysian community is still faced with many challenges in order to actively engage oneself in these activities. Literature shows that studies on motivation and barriers of outdoor recreational activities have been conducted in the past, however they do not focus on understanding the subject matter among rural and urban communities. Some of the factors that have been highlighted in which leads to the decreasing involvement of outdoor recreation activities during a person’s free time are the influence of technological advancement, preferring a sedentary lifestyle, the threat of infectious disease and outbreaks, and the availability of open spaces and limited recreation. This quantitative research study therefore, aimed at identifying the motivational factors for outdoor recreation involvement as well as the constraints that hinder individual involvement by including a number of 384 residents in Ipoh, Perak from two different categories of these areas through a questionnaire which was developed and distributed among sports and recreation clubs in Ipoh.